Analysis of the Factors Affecting Pharmaceutical Services in Patient Patients at Hospital TK. II dr. Soepraoen Malang - Sisworo, Dwi; Koesnadi; Suprapto, Sentot Imam (Journal for Research in Public Health, 2020)
With the increasing economic status of the community, the ease of communication and increased knowledge as a result of national development in all fields has caused the community to demand health services that are more qualified, friendly and able to meet their needs. The purpose of the study was to analyze the factors that influence pharmacy services in outpatients at TK Hospital. II dr. Soepraoen Malang. The research design used is quantitative research with a cross sectional approach. Instrument data used questionnaire sheets using Logistic Regression. The results of the chi square test analysis between variables affecting the service of pharmacy with service accuracy obtained p-value 0.001 for the variable accuracy, p-value 0,000 for the speed variable and p-value 0.003 for the satisfaction variable, p-value value < 0.05 then H0 is rejected and H1 is accepted, meaning that there is a relationship between pharmacy services with accuracy, speed and satisfaction of services in outpatients at TK Hospital. II Dr. Soepraoen Malang. Based on the results of the Ordinal Regression Test analysis shows that the most influential variable is the variable patient satisfaction with a p-value of 0,000 <0,05, then H0 is rejected and H1 is accepted so it is concluded that there is a significant relationship between Pharmacy Services and Satisfaction in Outpatients in TK Hospital. II Dr. Soepraoen Malang. It is expected that respondents can get the best service from Hospital Pharmacy Installation officers by means of accuracy, speed and patient satisfaction can be interpreted